CASPorter: A Novel Inducible Human CASP1/NALP3/ASC Inflammasome Biosensor - Zou C; Beard JA; Yang G; Evans WE; Bonten EJ (Dove Medical Press, 2022)
Chan Zou,1,2 Jordan A Beard,1 Guoping Yang,2- 4 William E Evans,1 Erik J Bonten1,5 1Department of Pharmaceutical Sciences, St. Jude Children's Research Hospital, Memphis, TN, USA; 2Center for Clinical Pharmacology, The Third Xiangya Hospital, Central South University, Changsha, Hunan, People's Republic of China; 3Department of Pharmacy, The Third Xiangya Hospital, Central South University, Changsha, Hunan, People's Republic of China; 4Research Center for Drug Clinical Evaluation of Central South University, Changsha, Hunan, People's Republic of China; 5Department of Chemical Biology and Therapeutics, St. Jude Children's Research Hospital, Memphis, TN, USACorrespondence: Erik J Bonten, Department of Chemical Biology and Therapeutics, St. Jude Children's Research Hospital, Memphis, TN, USA, Tel +1 901 595-3980, Fax +1 901 5955715, Email Erik.Bonten@stjude.org Guoping Yang, Center for Clinical Pharmacology, the Third Xiangya Hospital, Central South University, Changsha, Hunan, People's Republic of China, Tel/Fax +86 731 88618933, Email ygp9880@126.comBackground: Following our 2015 elucidation of the CASP1/NALP3 inflammasome mechanism of glucocorticoid (GC)-resistance in pediatric acute lymphoblastic leukemia (ALL) patients, we engineered a cell-based CASP1/NALP3 reporter system suitable for high-throughput screening (HTS) of small molecule libraries, with the purpose of identifying compounds capable of inhibiting the CASP1/NALP3 inflammasome and synergizing with GC drugs for the treatment of GC-resistant ALL patients and various autoinflammatory diseases.Methods: A Dox-controlled system was utilized to induce the expression of the ASC transgene in HEK293 cells while simultaneously overexpressing NLRP3 and CASP1. ASC/CASP1/NALP3 inflammasome complex formation was confirmed by co-immunoprecipitation (co-IP) experiments. Next, a LV fluorescence-based biosensor (CASPorter) was transduced in the HEK293-iASC-NLRP3/CASP1 cell line to monitor the real-time activation of CASP1/NALP3 inflammasome in live cells. The applicability and effectiveness of the CASPorter cell line were tested by co-treatment with Dox and four known CASP1/NLRP3 inhibitors (MCC950, Glyburide, VX-765 and VRT-043198). Inflammasome activation and inhibitions were assessed by Western blotting, fluorescence microscopy and flow cytometry (FC) methods.Results: Dox treatment significantly induced ASC expression and increased levels of cleaved and catalytically active CASP1, co-IPs further demonstrated that CASP1 was pulled-down with NLRP3 in HEK293-iASC-NLRP3/CASP1 cells after induction of ASC by Dox treatment. In HEK293-iASC-NLRP3/CASP1-CASPorter cell system, cleavage of the CASP1 consensus site (YVAD) in the CASPorter protein after Dox treatment causing excitation/emission of green fluorescence and the 71% GFP+ cell population increase quantified by FC (78.1% vs 6.90%). Dox-induced activation of the NLRP3 inflammasome was dose-dependently inhibited by Dox co-treatment with four known CASP1/NLRP3 inhibitors.Conclusion: We have established a cell-based CASP1/NLRP3 inflammasome model, utilizing a fluorescence biosensor as readout for qualitatively observing and quantitatively determining the activation of caspase 1 and NLRP3 inflammasomes in living cells and easily define the inhibitory effect of inhibitors with high efficacy.Keywords: cell-based biosensor, NALP3 inflammasome, CASP1, ASC